2015
DOI: 10.1016/j.fertnstert.2015.07.809
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs and ovarian reserve disorders

Abstract: between November 2013 and March 2014. Total 2085 patients underwent an ultrasound scan (Voluson 730, GE Healthcare, Istanbul, Turkey) by one of the two physicians (C.P. or Z.D.) between days 1 and 12 of the menstrual cycle. Inclusion criteria were (1) age 20 -50, (2) regular menstrual bleeding between 21 to 35 days, and (3) optimal visualization of both ovaries. The exclusion criteria were (1) hirsutism or menstrual irregularity, (2) any hormonal drug or oral contraceptive pill use within the last 6 months, (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A few studies reported that polymorphisms in miRNA may also change miRNA levels, thus altering metabolic parameters. A better understanding of the regulation of miRNAs may offer a theoretical foundation for ovarian diseases (12). This comprehensive review specifically looks at the aberrant expression of a multitude of microRNAs implicated in PCOS.…”
mentioning
confidence: 99%
“…A few studies reported that polymorphisms in miRNA may also change miRNA levels, thus altering metabolic parameters. A better understanding of the regulation of miRNAs may offer a theoretical foundation for ovarian diseases (12). This comprehensive review specifically looks at the aberrant expression of a multitude of microRNAs implicated in PCOS.…”
mentioning
confidence: 99%